Rumen ciliate protozoal fauna of reindeer in Inner Mongolia, China - Imai, S. (Nippon Veterinary and Animal Science Univ., Musashino, Tokyo (Japan)); Oku, Y; Morita, T; Ike, K; Guirong (Journal of Veterinary Medical Science, 2004)
Rumen ciliate species and composition were surveyed on the reindeer kept in Inner Mongolia, China. As a result of survey, all the reindeer had the same 18 species of 8 genera of the ciliates in their rumen. Appearance of Entodinium parvum is the first record in this host species. Of the species detected, 15 species including Entodinium anteronucleatum, E. bicornutum, Enoploplastron confluens and Epidinium gigas which have been detected only from reindeer were common with those in the reindeer kept in the other areas, such as Alaska, Russia and Finland, indicating that every rumen ciliate faunae in reindeer has high similarity to each other, and suggesting that these hosts have been isolated from the other ruminants for long time and established characteristic ciliate fauna. The ciliate density was estimated as 1.1-2.5 × 10 6/ml, which value was fairly higher than those in domestic ruminants. Surface structures of characteristic species were observed by SEM.